1997
DOI: 10.1006/viro.1996.8406
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of the Monopartite Tomato Yellow Leaf Curl Geminivirus: Roles of V1, V2, and C2 ORFs in Viral Pathogenesis

Abstract: Tomato yellow leaf curl virus (TYLCV) is a whitefly-transmitted geminivirus with a monopartite genome. We have investigated the functions of the V1, V2, and C2 ORFs by mutational analysis. We analyzed the ability of TYLCV mutants containing disrupted ORFs V1, V2, or C2 to replicate, spread, and cause symptoms in Nicotiana benthamiana and tomato plants. All the mutants retained the capability of autonomous replication in protoplast-derived cells of tomato and leaf discs of N. benthamiana, although both V1 and V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
1
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(72 citation statements)
references
References 44 publications
3
64
1
4
Order By: Relevance
“…Among them, C2 from several begomoviruses has been shown to be needed for viral propagation (Etessami et al, 1988;Wartig et al, 1997). To confirm if this is also applicable to Tomato yellow leaf curl Sardinia virus Spain isolate (TYLCSV; accession number L27708), one of the begomoviruses responsible for the Tomato yellow leaf curl disease (TYLCD) in Spain, we constructed a null mutant virus for the C2 gene with a T-C transition in the start codon, hereafter called TYLCSV C2 T2C .…”
Section: Tylcsv C2 Is Required For Full Infectionmentioning
confidence: 99%
“…Among them, C2 from several begomoviruses has been shown to be needed for viral propagation (Etessami et al, 1988;Wartig et al, 1997). To confirm if this is also applicable to Tomato yellow leaf curl Sardinia virus Spain isolate (TYLCSV; accession number L27708), one of the begomoviruses responsible for the Tomato yellow leaf curl disease (TYLCD) in Spain, we constructed a null mutant virus for the C2 gene with a T-C transition in the start codon, hereafter called TYLCSV C2 T2C .…”
Section: Tylcsv C2 Is Required For Full Infectionmentioning
confidence: 99%
“…However, gene function has been studied extensively in other types of geminiviruses which share organization and nucleotide sequence similarities with TYLCV. Mutational analysis of few monopartite begomoviruses like TYLCV define similarities and differences between this single component geminivirus and bipartite geminiviruses in functions essential for systemic spread and infectivity [103]. The CP appeared to be required for systemic movement of TYLCV in N. benthamiana and tomato, consistent with those of mutation analyses obtained with other monopartite geminiviruses such as MSV, BCTV, and TLCV [5,12,69,61] have shown that Tomato yellow leaf curl virus-Sardinia (TYLCV-Sar) C2 can form stable complexes with ssDNA (and less preferably with dsDNA) and that the binding is sequence nonspecific.…”
Section: Mutagenesis Of Effectors Encoded By Monopartite Begomovirusesmentioning
confidence: 99%
“…In fact, the PQ mutants, which are unable to assemble virions, accumulate CP in leaf discs, showing that its expression and stability were not altered. Another TYLCV protein, V2, for which a role in virus assembly has recently been, suggested [103].…”
Section: Mutated Orf Mutation Position Type Of Mutationmentioning
confidence: 99%
“…Encoded proteins are the CP (V1 ORF), the capsid protein; the replication-associated protein (Rep, C1 ORF), a protein essential for replication; the transcriptional activator protein (TrAP, C2 ORF), involved in the activation of the transcription of virus sense genes; the replication enhancer protein (REn, C3 ORF), which interacts with C1 protein enhancing viral DNA accumulation; and protein products encoded by the V2 «precoat» and C4 ORFs, that have been involved in symptom expression and virus movement. The noncoding IR region contains key elements for the replication and transcription of the viral genome including the origin of replication, within a stem-loop structure conserved in the geminiviruses (Jupin et al, 1994;Wartig et al, 1997;Noris et al, 1998).…”
Section: The Tomato Yellow Leaf Curl Disease and Associated Virusesmentioning
confidence: 99%